From the experience of conducting linguistic analysis of contentious advertising and information texts (Eurasian Journal of Philology Science and Education, 2018)
In modern society, one of the reasons for various kinds of information disputes are interpretations of advertising discourse, which occupies a special place in the media. In this regard, advertising texts, used to belittle business reputation in the marketing of companies that produce the same products or provide the same services, require a linguistic analysis. Within this framework, this article analyses the semantics of linguistic units of the advertising text of one company, which advertises its services in order to increase the demand for them. Functional-communicative functions of the superlative, metaphors forming the image of the given company are considered. The statement is considered as a form of factual information that is checked for compliance with reality in the advertising text. The author considers advertising texts containing inaccurate information, generating in the light of competition, and the language conflicts as information disputes.